RELIGIOSITY MODERATION ON THE EFFECT OF WHISTLEBLOWING INTENTION AND FRAUD TENDENCY - Veni Nopeanti; Tarjo Tarjo; Bambang Haryadi (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
This study examined the effect of whistleblowing intention on fraud tendency and the role of religiosity as a moderating variable of the effect of whistleblowing intention on fraud tendency in higher education institutions. The sample in this research was finance staff at State Universities in East Java. The research data were obtained by distributing questionnaires directly to the respondents. The methods used for data analysis in this research were simple linear regression and Moderated Regression Analysis (MRA). The results show that whistleblowing intention has an effect on fraud tendency. Besides, religiosity is also proven to be a moderating variable of whistleblowing intention effect on fraud tendency in higher education institutions.